1977
DOI: 10.1139/v77-333
|View full text |Cite
|
Sign up to set email alerts
|

Metal complex catalyzed reactions of anils. III. Kinetic and mechanistic studies

Abstract: The kinetics of the homogeneously catalyzed formation and hydrolysis of anils in non-aqueous solution have been studied. The catalysts used are zinc complexes of thiourea. It is shown that all the evidence obtained, kinetic and otherwise, is consistent with a model in which the rate determining step for anil formation is nucleophilic attack by an aniline held in the second coordination sphere of the metal complex on an acetone molecule directly bound to the metal atom. Analogous mechanisms are suggested for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Mechanistic Aspects. To obtain a first indication on the mechanistic pathway, the reaction of 1 with benzaldehyde (1:1 ratio) was performed at 25 °C in the presence of 4 mol % of Sc(OTf) 3 . After 3 days, no cross-product could be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic Aspects. To obtain a first indication on the mechanistic pathway, the reaction of 1 with benzaldehyde (1:1 ratio) was performed at 25 °C in the presence of 4 mol % of Sc(OTf) 3 . After 3 days, no cross-product could be detected.…”
Section: Resultsmentioning
confidence: 99%
“…These thiourea complexes are effective catalysts for a variety of anil formation and transimination reactions [85][86][87][88]. A kinetic study demonstrated that in anil formation, for example, both the aniline and the ketone were associated with the catalytically active metal complex during the rate determining step [86]. It was suggested that the ketone was present in the first coordination sphere and the aniline hydrogen bonded in the outer sphere, as was observed in the cobalt boronpyrazolate studies described above.…”
Section: The Mechanistic Role Of Outer Sphere Complexesmentioning
confidence: 82%
“…The ligand exchange reactions of related complexes of Ni(II) and Zn(II) were also studied [83,84] an.d it seems probable that the mechanisms are similar. These thiourea complexes are effective catalysts for a variety of anil formation and transimination reactions [85][86][87][88]. A kinetic study demonstrated that in anil formation, for example, both the aniline and the ketone were associated with the catalytically active metal complex during the rate determining step [86].…”
Section: The Mechanistic Role Of Outer Sphere Complexesmentioning
confidence: 99%